Implementasi Algoritma Cosine Similarity pada sistem arsip dokumen di Universitas Islam Sultan Agung - Kurniadi, Dedy; Haviana, Sam Farisa Chaerul; Novianto, Andika (Jurnal Transformatika, 2020)
Archiving in University that have not been well organized will cause a problems, the documents need for structuring and archives properly in the systems for the good standard a universities. The most importance of ease in finding the required archives is an important reason why it is necessary to develop an archive search system that can facilitate and improve the process of searching the archived document. Apllying cosine similarity algorithm in Information Systems is a solution for University to organizing archived documents, results from this reserach is the systems can show the relavant document from database list with precision 88.8% and recall 76.1% from all the data in database.